Midwifery Antenatal Care of Mrs "S" Gestation 38 Week 1 Day with Hypertension in Health Watampone District of Bone (Jurnal Suara Kesehatan, 2021)
Gestation period is a condition that requires attention, especially the health of the mother and fetus or baby. One thing that pregnant women need to watch out for is hypertension that occurs in pregnancy, because hypertension in pregnancy is a pregnancy complication of 5-15% and is one of the three causes of death and the highest maternal morbidity. In this study, the midwifery care management process approach was applied which included 7 varney steps, namely: basic data collection, identification of actual diagnosis / problems, identification of diagnosis / potential problems, determining the need for immediate action or collaboration, compiling a treatment plan, treatment management and evaluation. Data collection was carried out by anamnesis / interviews with clients, husbands, and families to obtain the data needed to provide midwifery care to clients. The method used in the preparation of this research includes literature studies, case studies using the midwifery care management process approach which includes 7 varney steps, namely: basic data collection, identification of actual diagnosis / problems, identification of diagnosis / potential problems, determining the need for action or immediate collaboration, develop care plans, care management and evaluation. The results showed that from the results of data identification and analysis of basic data in the case of Ny. "S" was found that the mother complained of frequent dizziness, headaches and had a physical examination with a blood pressure of 140/90 mmHg. This is the same as the theory of signs and symptoms of hypertension in pregnant women. This shows that there is no gap between theory and practice. Mrs "S" diagnosis / real problem is hypertension that is enforced in pregnancy. In the diagnosis or actual problems in the use of midwifery care approaches are supported and supported by some data. From the analysis and data on the case of Mrs. "S" with hypertension in pregnancy, then the diagnosis / potential problem of preeclampsia was obtained from the case of Mrs. "S" with hypertension in pregnancy collaborative action with doctors in the medical field